KEMAMPUAN FONOLOGI PADA MEMBACA TEKS STUDI KASUS DANI ARDIAN DI PONTIANAK - Latifah, Rossy Azra; Patriantoro, Patriantoro; Jupitasari, Mellisa (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
This research aims to describe phonological ability in Dani's pronunciation while reading a text, particularly concerning the deletion, addition, and substitution of phonemes. The method employed is qualitative research with a descriptive approach, utilizing Dani's reading data from Pontianak as the focal point of analysis. Primary data, consisting of observations, tests, interviews, recordings, and notations, forms the basis for understanding Dani's reading approach. Through data collection techniques such as observation, testing, interviewing, recording, and note-taking using devices and record sheets, the research identified phonological errors including inconsistent word shortening due to the deletion of sounds at the beginning and end of words, as well as additional sounds like vowels between consonants in various word positions. This research can enhance understanding of aphasia as a communication disorder that affects reading, writing, numerical skills, and conversation comprehension. It also serves as a significant reference in the field of linguistics for further research.